Mutual comparison of developed actuators for robotic arms of service robots. (22nd November 2017) - Semjon, Jan; Janos, Rudolf; Sukop, Marek; Vagas, Marek; Varga, Jozef; Hroncova, Darina; Gmiterko, Alexander
Development and deployment of new drives using reducers is exactly dependent on their area of application. Designing a universal drive is complex and cannot be done without various compromises. When installing the drives into the robotic arm nodes used on the chassis of the mobile service robots, it is also necessary to provide suitable input voltage values for operation on the built-in batteries. To provide the desired results, it is sometimes more suitable to have actuators with various configurations which, however, leads to the need for a comparison between them. Testing stands of drive manufacturers are designed to test drive parameters that are standard version. For the development of new drive configuration with the use of secondary transfer, it is necessary to implement the specific verification stands, which allows for comparison between the properties under the same test conditions. Drives equipped with accurate reducers are very sensitive to the choice of the correct methodology for measuring, because their declared repeatability is less than 1.5 arcmin. The article describes the relative positioning accuracy of the resulting configurations of the two actuators, one of which uses a secondary belt drive and the other uses a flexible coupling for linking the motor and the reducer. For the avoidance of production inaccuracies, the motor and reducer on the measured drives are the same. This means that before the verification of the first drive, it is necessary to assemble the whole system, according to the prescribed manufacturing process. After implementing the measurement, the same components are used, namely the engine and the reducer of the other drive, and the measurement is carried out under the same conditions.